Rancang Bangun Sistem Informasi Manajemen Data Kelompok Tani dan Pembagian Subsidi Berbasis Web : (Studi Kasus: Balai Penyuluhan Pertanian Kecamatan Batang Asai) - Febi Kurniawan; Mhd. Theo Ari Bangsa; Fatimah Felawati (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This research ams to design and develop a web-based information system for managing farmer group data and subsidy distribution at the Agricultural Extension Center (BPP) of Batang Asai District. The system was developed to address problems in manual data management, which often lead to administrative delays, data inaccuracies, and a lack of transparency in subsidy distribution. The research method used is Research and Development (R&D) with the Waterfall development model, which consists of requirements analysis, system design, implementation, and testing. Requirements analysis was carried out through interviews,observations, documentation, and literature study. The system design utilized Unified Modeling Language (UML) diagrams (Use Case, Activity, Class, and Sequence Diagram) and was implemented using PHP Native and MySQL as the database. Testing was performed using the blackbox testing method to ensure the system works according to user requirements. The result of this study is a web-based information system that enables integrated management of farmer group data, member data, production data, subsidy applications, verification, and report generation. The system is equipped with rolebased access control (administrator, village admin, and farmer group leader) to support accuracy, efficiency, and transparency in data management and subsidy distribution processes.